CSRR slotted CPW-Fed Compact Antenna for UWB Applications - Kancherla, Praveen Kumar; Boyina, Amulya (International Journal of Psychosocial Rehabilitation, 2020)
A compact monopole antenna having CPW-Fed provided with CSRR slots which produce dual notch band characteristics are presented and its results are analyzed. To obtain dual notch band characteristics in UWB against neighbourhood interfering bands, the CSRRs are used. The architecture contains CSRRs etched on patch and ground. Rogers RT/duroid 5880 material with a stature of 0.8mm of surface area 30x30mm2 is used. The proposed antenna shows its impedance bandwidth that covers the ultra-wide band which is spread across 3.1GHz to 10.6 GHz for VSWR ≤ 2 and exist dual band notches of 3.3GHz to 3.7 GHz and 5.15GHz to 5.825GHz to mitigate the interference from existing Wi-MAX and WLAN bands. The designs of antenna, geometrical parameters and simulations have been carried out by using the HFSS tool. Design procedure, parametric studies and obtained results were presented.